China Registry of Hepatitis B (CR-HepB): Protocol and implementation of a nationwide hospital-based registry of hepatitis B. Issue 2 (March 2020) - Shan, Shan; Wei, Wei; Kong, Yuanyuan; Niu, Junqi; Shang, Jia; Xie, Wen; Zhang, Yuexin; Ren, Hong; Tang, Hong; Ding, Huiguo; Nan, Yuemin; Dou, Xiaoguang; et al.
Aims: The disease burden of chronic HBV infection in China remains high, although the rate of new infections has become extremely low. To facilitate real-world clinical study of chronic HBV infection, we established a nationwide hospital-based electronic platform, named the China Registry of Hepatitis B (CR-HepB). Methods: This internet-based registry for chronic hepatitis B recruited patients from tertiary or secondary hospitals that have particular interest and expertise in managing hepatitis B patients. The main inclusion criteria for the database were men or women with hepatitis B surface antigen positivity ≥ 6 months, hepatitis B e antigen positive or negative, with or without cirrhosis, and with or without treatment. At the first time of data entry, demographics, medical history, virology, biochemistry, hematology and radiology reports, as well as diagnosis and treatment information, are recorded. Registered patients then receive a standard of care and follow-up every three (optional) to six months (required) for changes in virology, biochemistry and radiology, as well as clinical progression. Results and Conclusions: To date, 47 hospitals have joined the CR-HepB. This platform can be used to demonstrate the clinical pattern and treatment profile of chronic HBV infection, evaluate long-term efficacy and safety of antiviral therapy and provide real-world evidence for policy-making in China. Trial registration: ClinicalTrials.gov ID: NCT03108794